Prevalence and correlates of diagnosed and undiagnosed type 2 diabetes mellitus and pre-diabetes in older adults: Findings from the Irish Longitudinal Study on Ageing (TILDA). - Kenny, Rose; O'Halloran, Aisling (My University, 2015)
Aims: The prevalence of type 2 diabetes and pre-diabetes has increased rapidly in recent decades and this trend will continue as the global population ages. This study investigates the prevalence of, and factors associated with, diagnosed and undiagnosed type 2 diabetes mellitus and pre-diabetes in older adults in Ireland. Methods: Cross-sectional data from 5377 men and women aged 50 and over from Wave 1 of the Irish Longitudinal Study on Ageing (TILDA) was analysed. Diagnosed diabetes was defined using self-reported doctors' diagnosis and medications data. Glycated haemoglobin (HbA1c) analysis was used to identify undiagnosed and pre-diabetes. Age and sex-specific prevalence estimates were generated. Logistic regression was used to investigate the association between diabetes classification and the demographic, health and lifestyle characteristics of the population. Results: The prevalence of diagnosed and undiagnosed type 2 diabetes was 8.6% (95% confidence interval (CI): 7.6-9.5%) and 0.9% (95% CI: 0.6-1.1%) respectively. Diabetes was more prevalent in men than women and increased with age. The prevalence of pre-diabetes was 5.5% (95% CI: 4.8-6.3%) and increased with age. Diabetes and pre-diabetes were independently associated with male sex, central obesity and a history of hypertension, while undiagnosed diabetes was associated with geographic location and medical costs cover. Conclusion: Despite high rates of obesity and other undiagnosed health conditions, the prevalence of undiagnosed and pre-diabetes is relatively low in community-dwelling older adults in Ireland. Addressing lifestyle factors in this population may help to further reduce the prevalence of pre-diabetes and improve outcomes for those with a previous diagnosis. Keywords:
Keywords: Ageing; Diabetes mellitus, Type 2; HbA1c; Prediabetes; Prevalence; Undiagnosed; Ageing; Chronic Health Condition; Health; Third age/ageing